Working 9 to Non-Stop: The Fair Housing Act’s Sexual Harassment Protections for Domestic, Agricultural, and Other Live-In Workers - Lowell, Callen (Columbia Journal of Gender and Law, 2021)
Live-in workers, for whom their bosses are typically also their landlords, are often trapped in sexually harassing situations that feel as though they have no practical or legal redress, especially when the worker’s harasser can both fire and evict them in one fell swoop. This Note explores the novel possibility of using fair housing law, including the Fair Housing Act (“FHA”) and state/local fair housing statutes, as a tool to provide legal protections to workers with employer-provided housing (“live-in workers”) who experience sexual harassment or violence in the workplace. There is currently very little case law in which live-in workers have brought fair housing and employment discrimination claims simultaneously, and functionally no case law in which attorneys have brought both claims for live-in worker sexual harassment cases. This Note argues that, under existing fair housing law, many live-in workers should be eligible to bring claims under the FHA and equivalent state laws that prohibit discrimination in housing. As a result, the FHA and equivalent state claims can provide sexual harassment and assault protections for workers, including domestic workers and farmworkers, who may not receive protections under federal or state employment discrimination law. Furthermore, this Note argues that the FHA can provide supplemental or stronger protections from sexual harassment for live-in workers than traditional Title VII or employment discrimination claims. It accordingly suggests that plaintiffs facing harassment or sexual assault in live-in industries should pursue fair housing claims in addition to or in place of Title VII and employment discrimination claims, in order to achieve maximum protection and relief.